Korporacje transnarodowe a zjawisko luki technologicznej w krajach rozwijających się - Kraciuk, Jakub (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
The aim of the paper was to present a technological gap problem, noticed between developed countries and developing countries, as well as methods of minimizing the gap. Moreover, the author compared measures of innovation creation in different countries and indicated problems with implementation National Innovation Systems in developing countries. Finally, signi? cance of new technologies transfer in developing countries’ economic development and role of transnational corporations in the transfer were described.